2019
DOI: 10.1126/sciadv.aav2104
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting the stringent response blocks Mycobacterium tuberculosis entry into quiescence and reduces persistence

Abstract: The stringent response enables Mycobacterium tuberculosis (Mtb) to shut down its replication and metabolism under various stresses. Here we show that Mtb lacking the stringent response enzyme RelMtb was unable to slow its replication rate during nutrient starvation. Metabolomics analysis revealed that the nutrient-starved relMtb-deficient strain had increased metabolism similar to that of exponentially growing wild-type bacteria in nutrient-rich broth, consistent with an inability to enter quiescence. Deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
127
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(133 citation statements)
references
References 59 publications
1
127
0
Order By: Relevance
“…(p)ppGpp has recently been shown to bind to Era from Staphylococcus aureus and E. coli to inhibit its GTPase activity ( 3941 ), and this may influence ribosome biogenesis and integrity. There is good evidence that (p)ppGpp is important for development of antibiotic persisters ( 42 ) and for long term survival of latent and growth-arrested M. tuberculosis ( 43, 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…(p)ppGpp has recently been shown to bind to Era from Staphylococcus aureus and E. coli to inhibit its GTPase activity ( 3941 ), and this may influence ribosome biogenesis and integrity. There is good evidence that (p)ppGpp is important for development of antibiotic persisters ( 42 ) and for long term survival of latent and growth-arrested M. tuberculosis ( 43, 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the finding that a M. tuberculosis mutant missing PPX1 is associated with elevated intracellular poly P and tolerance to INH ( Thayil et al, 2011 ), whereas a mutant devoid of PPK1 is associated to low levels of poly P and increased drug susceptibility ( Singh et al, 2013b ). In a recent work, Dutta et al (2019) demonstrated that a M. tuberculosis rel mtb null mutant was unable to accumulate poly P and down-modulate metabolism to decrease growth rate in a condition of nutrient starvation. While the INH minimal bactericidal concentration (MBC) of the mutant strain and its parental strain were equal in rich media, during nutrient starvation the wild type strain MBC increased 512-fold, whereas that of the mutant strain remained equal, suggesting that the stringent response activation was responsible for tolerance to this drug.…”
Section: Role Of Stringent Response In Tolerance To Drugsmentioning
confidence: 99%
“…While the INH minimal bactericidal concentration (MBC) of the mutant strain and its parental strain were equal in rich media, during nutrient starvation the wild type strain MBC increased 512-fold, whereas that of the mutant strain remained equal, suggesting that the stringent response activation was responsible for tolerance to this drug. Interestingly, enhanced susceptibility to INH of the rel mtb null mutant was also demonstrated during the chronic phase of infection in BALB/c mouse lungs ( Dutta et al, 2019 ). The finding that (p)ppGpp-mediated tolerance to INH was detectable only upon nutrient starvation, well explains the contrasting data obtained by Bhaskar et al (2018) , who did not show any tolerance to INH in different M. smegmatis mutants missing rel mtb , lon , ppk1 , ppk2 , or both ppx1 and ppx2 , as these authors run their experiments in cultures growing exponentially in rich medium, a condition not activating the stringent response.…”
Section: Role Of Stringent Response In Tolerance To Drugsmentioning
confidence: 99%
“…Arresting the (p)ppGpp synthetase activity using (p)ppGpp analogues is emerging as a clinically important method in eradicating persistent infections ( de la Fuente-Núñez et al, 2014 ; Andresen et al, 2016 ; Petchiappan and Chatterji, 2017 ; Syal et al, 2017 ; Dutta et al, 2019 ). Similarly, the ssRNA-binding property of the SAS can be explored to regulate the SAS-mediated (p)ppGpp synthesis.…”
Section: Sas Bind To Ssrnamentioning
confidence: 99%